Antimalarial activity of artefenomel (OZ439), a novel synthetic antimalarial endoperoxide, in patients with Plasmodium falciparum and Plasmodium vivax malaria: an open-label phase 2 trial. Issue 1 (January 2016) - Phyo, Aung Pyae; Jittamala, Podjanee; Nosten, François H; Pukrittayakamee, Sasithon; Imwong, Mallika; White, Nicholas J; Duparc, Stephan; Macintyre, Fiona; Baker, Mark; Möhrle, Jörg J
Summary: Background: Artefenomel (OZ439) is a novel synthetic trioxolane with improved pharmacokinetic properties compared with other antimalarial drugs with the artemisinin pharmacophore. Artefenomel has been generally well tolerated in volunteers at doses up to 1600 mg and is being developed as a partner drug in an antimalarial combination treatment. We investigated the efficacy, tolerability, and pharmacokinetics of artefenomel at different doses in patients with Plasmodium falciparum or Plasmodium vivax malaria. Methods: This phase 2a exploratory, open-label trial was done at the Hospital for Tropical Diseases, Bangkok, and the Shoklo Malaria Research Unit in Thailand. Adult patients with acute, uncomplicated P falciparum or P vivax malaria received artefenomel in a single oral dose (200 mg, 400 mg, 800 mg, or 1200 mg). The first cohort received 800 mg. Testing of a new dose of artefenomel in a patient cohort was decided on after safety and efficacy assessment of the preceding cohort. The primary endpoint was the natural log parasite reduction per 24 h. Definitive oral treatment was given at 36 h. This trial is registered withClinicalTrials.gov, numberNCT01213966 . Findings: Between Oct 24, 2010, and May 25, 2012, 82 patients were enrolled (20 in each of the 200 mg, 400 mg, and 800 mg cohorts, and 21 in the 1200 mg cohort). One patient withdrew consent (before the administration of artefenomel) but there were no further dropouts. The parasite reduction rates per 24 h ranged from 0·90 to 1·88 for P falciparum, and 2·09 to 2·53 for P vivax . All doses were equally effective in both P falciparum and P vivax malaria, with median parasite clearance half-lives of 4·1 h (range 1·3–6·7) to 5·6 h (2·0–8·5) for P falciparum and 2·3 h (1·2–3·9) to 3·2 h (0·9–15·0) for P vivax . Maximum plasma concentrations, dose-proportional to 800 mg, occurred at 4 h (median). The estimated elimination half-life was 46–62 h. No serious drug-related adverse effects were reported; other adverse effects were generally mild and reversible, with the highest number in the 1200 mg cohort (17 [81%] patients with at least one adverse event). The most frequently reported adverse effect was an asymptomatic increase in plasma creatine phosphokinase concentration (200 mg, n=5; 400 mg, n=3; 800 mg, n=1; 1200 mg, n=3). Interpretation: Artefenomel is a new synthetic antimalarial peroxide with a good safety profile that clears parasitaemia rapidly in both P falciparum and P vivax malaria. Its long half-life suggests a possible use in a single-dose treatment in combination with other drugs. Funding: Bill & Melinda Gates Foundation, Wellcome Trust, and UK Department for International Development.